Penerapan Pengembangan Permainan Congklak Sebagai Media Pembelajaran Pada Materi Bangun Datar Di Kelas III SD - Diana Rosa Nuraisha; Andika Arisetyawan (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Ethnomathematics is a form of mathematics based on culture. Through the application of ethnomathematics in education, especially mathematics education, it is hoped that later students can better know and understand our own culture and educators can also more easily instill cultural values ​​themselves in students, so that cultural values ​​that should be part of the nation's character can be embedded early on in students. One of them is by using the traditional game of Congklak. One of the games that can be used in learning mathematics is the traditional game of congklak which is considered suitable in the material of two-dimentional figure where in it’s section there are several shapes of two-dimentional figure, such as circles and rectangles. The game is not only used as a learning medium, but students can get to know more about the traditional game of congklak and so that the traditional game of congklak can continue to be preserved. Schools have a variety of learning media, but not all of these media contain elements of Indonesian culture, especially for mathematics. The researcher also uses a qualitative method with an ethnographic approach and a descriptive method using the ADDIE teaching material development model to explain the results of the research that has been done. The application of this media is said to have positive results from the field results obtained by researchers and from the results of interviews conducted afterwards. The use of this media can in fact be applied to learning media in the classroom because it’s use is easy and fun for students.